Telemedicine, Artificial Intelligence and Humanisation of Clinical Pathways in Heart Failure Management: Back to the Future and Beyond - Domenico D’Amario; Francesco Canonico; Daniele Rodolico; Josip A Borovac; Rocco Vergallo; Rocco Antonio Montone; Mattia Galli; Stefano Migliaro; Attilio Restivo; Massimo Massetti; Filippo Crea (Cardiac Failure Review)
New technologies have been recently introduced to improve the monitoring of patients with chronic syndromes such as heart failure. Devices can now be employed to gather large amounts of data and data processing through artificial intelligence techniques may improve heart failure management and reduce costs. The analysis of large datasets using an artificial intelligence technique is leading to a paradigm shift in the era of precision medicine. However, the assessment of clinical safety and the evaluation of the potential benefits is still a matter of debate. In this article, the authors aim to focus on the development of these new tools and to draw the attention to their transition in daily clinical practice.